Faktor Psikologis dalam Pembelajaran Matematika: Analisis Minat, Motivasi, dan Kemandirian Belajar Siswa - Patih, Tandri; Tarty, Indri Purnama; Halistin, Halistin; Sangila, Muh. Syarwa (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This quantitative research examines the influence of psychological factors such as interest, motivation, and learning independence on students' mathematics learning outcomes during online learning, using the causal research design. Data were analyzed using generalized linear models. The population consisted of all Grade VIII students at a public junior high school at Konawe Selatan, Southeast Sulawesi, Indonesia, totaling 273 students. A sample of 73 students was selected using a cluster random sampling technique. The results showed that only the variable of interest in learning mathematics had a significant effect on students' mathematics learning outcomes at a significance level of 5%. The findings indicate that as students' interest in learning increases, their mathematics learning outcomes improve by 0.56 points. In contrast, learning motivation and learning independence did not significantly affect students’ mathematics learning outcomes.